Implementation of The Precautionary Principle In The Making of Land Deeds To Avoid This Occurrence Land Certificate Duplication In Ambon City - Syafi'I, Muhammad Yusuf; Hasana, Dahniarti (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. This study examines the application of the precautionary principle by Land Deed Officials (PPAT) in making land deeds to prevent duplication of land certificates in Ambon City. Duplication of land certificates is a serious problem in Ambon City with 8 cases recorded in the last 14 years (2010-2023), although the number is smaller compared to big cities in Indonesia. This situation is exacerbated by several factors unique to Ambon City, namely the customary land ownership system (petuanan land/state land), the impact of the 1999 social conflict which caused many land documents to be damaged or lost, and weaknesses in land administration. The study used an empirical legal method with a statutory and conceptual approach. Data were obtained through interviews with PPAT and officials of the Ambon City Land Office, as well as documentation studies. The results of the study indicate that PPAT in Ambon City has implemented the principle of prudence through several steps: checking the identity and authority of the parties, checking the validity of land certificates, verifying supporting documents, coordinating with the Land Office and related agencies, providing legal counseling to the parties, and refusing to make a deed if there is an indication of incorrect data. Efforts to improve the effectiveness of the implementation of the precautionary principle include: increasing science and knowledge, modernizing the land service system, standardizing services and procedures, empowering professional organizations, strengthening law enforcement, and strengthening supervision and coaching mechanisms. Based on the SWOT analysis, increasing the effectiveness of the implementation of the precautionary principle of PPAT in Ambon City requires a comprehensive approach by utilizing existing strengths and opportunities, as well as overcoming weaknesses and anticipating threats.Keywords: Duplication of Certificates; Land Deed; Principle of Prudence; PPAT.